Ultra-Fast ASP.NET Building Ultra-fast and Ultra-scalable Web Sites Using ASP.NET and SQL Server - Kiessig, Richard; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Ultra-Fast ASP.NET presents a practical approach to building fast and scalable web sites using ASP.NET and SQL Server. In addition to a wealth of tips, tricks and secrets, you'll find advice and code examples for all tiers of your application, including the client, caching, IIS 7, ASP.NET, threads, session state, SQL Server, Analysis Services, infrastructure and operations. By applying the ultra-fast approach to your projects, you$1 (Bll squeeze every last ounce of performance out of your code and infrastructure$1 (Bgiving your site unrivaled speed. The approach is mostly prescriptive; rather than drowning you in options, the book presents and explains specific high-impact recommendations and demonstrates them with detailed examples. Using this knowledge, you will soon be building high-performance web sites that scale easily as your site grows.s
Principles and Method -- Client Performance -- Caching -- IIS 7 -- ASP.NET Threads and Sessions -- Using ASP.NET to Implement and Manage Optimization Techniques -- Managing ASP.NET Application Policies -- SQL Server Relational Database -- SQL Server Analysis Services -- Infrastructure and Operations -- Putting It All Together.
Keywords: Computer science; Computer Science; Programming Techniques